Increase Natural Serotonin Hormone with Pranayama Ante-Natal Yoga Method to Control Anxiety in Pregnant Women - Nicky Danur Jayanti; Senditya Indah Mayasari (Universitas Muhammadiyah Semarang, 2023)
The anxiety of pregnant women can be caused because the fear and fear that most pregnant women feel is anxiety and fear in facing childbirth. Anxiety will have a negative impact on pregnant women from pregnancy to delivery. The hormone serotonin as a mental health hormone that can prevent anxiety, mood, or depression can be produced by the body naturally. Some ways that you can increase the release of the hormone serotonin naturally are by exercising, massage, sunbathing in the sun, and meditation or yoga. Analyzing the increase in natural serotonin hormones with the pranayama antenatal yoga method to control anxiety in pregnant women. This research is quasi-experimental research, with a nonrandomized pretest-post-test control group design. The population in this study were pregnant women in the PMB